2013
DOI: 10.1097/ftd.0b013e31828e7e6b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of 26 Opioids, Cocaine, and Their Metabolites in Human Blood by Ultra Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: A sensitive and selective ultra performance liquid chromatographic-tandem mass spectrometric method was developed and fully validated for the simultaneous determination of (in order of chromatographic elution) methylecgonine, pholcodine, morphine, hydromorphone, oxymorphone, norcodeine, codeine, dihydrocodeine, oxycodone, 6-Monoacetylmorphine (6-MAM), hydrocodone, ethylmorphine, norfentanyl, benzoylecgonine, tramadol, normeperidine, meperidine, cocaine, pentazocine, cocaethylene, fentanyl, norbuprenorphine, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 24 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…The determination of such ME is therefore crucial to ensure a proper detection and quantification of the substances of interest. ME ranged from −51% (15% CV) of ion suppression for THC at low concentration and 3% (13% CV) of ion enhancement for lorazepam, being consistent with the existing literature (Table 3) (Simonsen et al, 2010;Fernandez Mdel et al, 2013;Montenarh et al, 2014;Steuer et al, 2014;Vaiano et al, 2016;De Boeck et al, 2017). All values concerning RE and ME are summarized in Table 3.…”
Section: Selectivity Recovery and Matrix Effectsupporting
confidence: 88%
“…The determination of such ME is therefore crucial to ensure a proper detection and quantification of the substances of interest. ME ranged from −51% (15% CV) of ion suppression for THC at low concentration and 3% (13% CV) of ion enhancement for lorazepam, being consistent with the existing literature (Table 3) (Simonsen et al, 2010;Fernandez Mdel et al, 2013;Montenarh et al, 2014;Steuer et al, 2014;Vaiano et al, 2016;De Boeck et al, 2017). All values concerning RE and ME are summarized in Table 3.…”
Section: Selectivity Recovery and Matrix Effectsupporting
confidence: 88%
“…Precision was determined at three different drug concentration levels in plasma (0.1, 0.5 and 5 μg ml -1 ), and the coefficients of variation were acceptable (Table 2). Napoletano et al (2012) obtained similar results, and other authors (Bassan et al, 2011;Dowling & Regan, 2011;Ramírez Fernández et al, 2013) also using LC-MS/MS for determinations reported higher precision values.…”
Section: Validation Of the Proposed Analytical Methodssupporting
confidence: 73%
“…Numerous analytical methods have been described for the quantitative determination of MEP, TRAM or dextropropoxyphene, alone or with their metabolites, in plasma samples. Gas chromatography/mass spectrometry (GC/MS) and liquid chromatography/mass spectrometry (LC/MS) are the main techniques used for most of these methods.…”
Section: Introductionmentioning
confidence: 99%